Isolamento e seleção de fungos filamentosos termofílicos/termotolerantes produtores de celulases e xilanases e aplicação dos extratos enzimáticos na sacarificação do bagaço de cana-de-açúcar - Pereira, Josiani de Cassia [UNESP] (2013)
Due to the expansion of industrial applications of cellulases and hemicellulases, there is increasing interest in the production of these enzymes by micro-organisms through processes that promote high yields at low cost. Thus, the cultivation of filamentous fungi by solid state fermentation (SSF) using lignocellulose residues as substrates has been frequently cited in the literature. The thermophilic fungi has excelled in this regard, since they produce enzymes usually more active and stable under high temperatures, an advantage from the point of view of industrial applications. In this work, 32 thermophilic fungi were isolated from the environment, from samples of silage, composting and other organic materials. An initial screening of the best producers was made by cultivation of isolates, by SSF, in a mixture of sugar cane bagasse and wheat bran (1:1 w/w) as substrates, for 96h. From these cultivations 7 isolates were pre-selected, which were then cultured by SSF in different mixtures of agro-industrial residues, for 96h, in order to assess the influence of these substrates in enzymes production, seeking higher yields. Then, were selected to give continuity to the work the isolates that stood out in the production of enzymes: Myceliophthora thermophila JCP 1-4 (endoglucanase, -glucosidase, xylanase and avicelase) and DABM 11/45 (-glucosidase, xylanase and avicelase). The influence of the time on the enzymes production by the two selected isolates was assessed and the enzymes were characterized physico-chemically. The enzymatic extract produced by M. thermophila, by FES, in a mixture of sugar cane bagasse and soybean meal (1:1 w/w) was used for the saccharification of in natura and pre-treated with ozone sugarcane bagasse. Saccharification assays were also performed with commercial enzymes, for comparative purposes. The in natura and ozonized bagasse were characterized regarding the content of cellulose, hemicellulose and lignin ...